Acute Photobiomodulation by LED Does Not Alter Muscle Fatigue and Cycling Performance - Dutra, Yago Medeiros [UNESP]; Claus, Gabriel MacHado [UNESP]; Malta, Elvis De Souza [UNESP]; Brisola, Gabriel Motta Pinheiro [UNESP]; Esco, Michael R.; Ferraresi, Cleber; Zagatto, Alessandro Moura [UNESP] (Wolters Kluwer, 2020)
Purpose The purpose of the present study was to investigate the ergogenic effects of two doses of photobiomodulation therapy (PBMT) in comparison to placebo on markers of respiratory and muscle activity, blood acid-base, ion and lactate concentrations, indicators of muscle fatigue (global, central, and peripheral), and time to exhaustion in severe-intensity cycling. Methods Two separate studies were performed, both in a pseudorandomized and balanced, crossover design. In study 1, 14 male recreational cyclists completed three constant-load, severe-intensity cycling bouts that were duration matched. The PBMT (18 × 38 cm array with 200 diodes) treatments occurred before bouts at 260, 130, or 0 J (placebo) doses. EMG activity of selected lower limb musculature was assessed during each bout. Maximal voluntary contractions of knee extension with peripheral nerve stimulations and EMG activity evaluation of vastus lateralis was also performed before and after cycling. In study 2, 13 recreational cyclists performed three bouts of constant-load, severe-intensity cycling until exhaustion, preceded by PBMT as detailed previously. Blood lactate concentrations, respiratory responses, EMG activity, and capillary gasometry aspects were monitored. Results In both studies, there were no interactions effects (time-condition) on the EMG activity, which was displayed as root mean square (P ≥ 0.168) and median frequency (P ≥ 0.055) during cycling. In study 1, there were no interaction effects on the indicators of muscle fatigue after exercise (P ≥ 0.130). In study 2, there were no differences on time to exhaustion (P = 0.353) and no interaction effects among the physiological responses monitored (P ≥ 0.082). Conclusions Based on our findings, the PBMT at 260- and 130-J doses does not have a beneficial effect on muscle fatigue, cycling performance, metabolic parameters, and muscle activity in male recreational cyclists.
Keywords: ERGOGENIC AID; LED THERAPY; LOW-LEVEL LASER THERAPY; PHYSICAL PERFORMANCE; TWITCH INTERPOLATION TECHNIQUE